La normative italiana sull'agricoltura sociale e il ruolo dell'impresa agricola - Francesca Giarè; Gabriella Ricciardi; Michela Ascani (Italian Review of Agricultural Economics (REA), 2020)
– In Italy, the regulatory framework on Social Farming has a high level of articulation at national and regional level and requires adequate analysis in order to understand the possible implications for the agriculture. The purpose of the article is to contribute to the understanding the possible interactions between farmers, local communities, public and private actors and recipients. The contribute, after a general analysis of the national and regional legislation, focuses on the figure of the SF operator and on the modalities of registration with the regional register. The question arises is whether and to what extent the regulatory framework on SF changes the role of agriculture itself with the system into which it operates, mainly about social aspects and relations with other local actors.
Keywords: O35; O20; I31; I38; Q18; 330; agricoltura sociale; normativa; impresa agricola; multifunzionalità; valore sociale